The Role of Merak Vessel Traffic Service (VTS) in the Implementation of Traffic Separation Scheme (TSS) in Sunda Strait - Ananda Firsta Tea Relevania Purnama; Atika Khoirul Umaroh; Setyo Nugroho (Department of Ocean Engineering, 2024)
Merak Vessel Traffic Service (VTS) is pivotal in Indonesia's critical maritime traffic network, particularly within the bustling Sunda Strait. This waterway holds immense strategic importance, serving as the primary link between Java and Su-matra Islands and intersecting with the vital Indonesian Archipelago Sea Lane. The Indonesian Government implemented a Traffic Separation Scheme (TSS) in July 2020 to enhance safety and navigation. Despite three years of TSS implementation, concerns persist regarding compliance and safety within the Sunda Strait. This research employs qualitative methods to address these concerns, chiefly in-depth interviews with VTS operators. The overarching objective is to gain profound insights into the intricacies of TSS implementation and the array of challenges it faces. The findings reveal several significant challenges. These include the lack of robust law enforcement and insufficient socialisation efforts regarding TSS regulations, concerns related to weather conditions impacting maritime operations, limitations in VHF radio modulation affecting communication, and issues surrounding vessel compliance with directives from VTS operators. In light of these challenges, future recommendations should prioritise strengthening law enforcement mechanisms, intensifying educational initiatives, improving communication technology, enhancing weather monitoring capabilities, and exploring ways to strengthen vessel compliance with VTS instructions.